Basin‐wide N2 fixation in the deep waters of the Mediterranean Sea. Issue 6 (30th June 2016) - Benavides, Mar; Bonnet, Sophie; Hernández, Nauzet; Martínez‐Pérez, Alba María; Nieto‐Cid, Mar; Álvarez‐Salgado, Xosé Antón; Baños, Isabel; Montero, María F.; Mazuecos, Ignacio P.; Gasol, Josep M.; Osterholz, Helena; Dittmar, Thorsten; et al.
Abstract: Recent findings indicate that N2 fixation is significant in aphotic waters, presumably due to heterotrophic diazotrophs depending on organic matter for their nutrition. However, the relationship between organic matter and heterotrophic N2 fixation remains unknown. Here we explore N2 fixation in the deep chlorophyll maximum and underneath deep waters across the whole Mediterranean Sea and relate it to organic matter composition, characterized by optical and molecular methods. Our N2 fixation rates were in the range of those previously reported for the euphotic zone of the Mediterranean Sea (up to 0.43 nmol N L −1 d −1 ) and were significantly correlated to the presence of relatively labile organic matter with fluorescence and molecular formula properties representative for peptides and unsaturated aliphatics and associated with the presence of more oxygenated ventilated water masses. Finally, and despite that the aphotic N2 fixation contributes largely to total water column diazotrophic activity (>50%), its contribution to overall nitrogen inputs to the basin is negligible (<0.5%). Key Points: Volumetric N2 fixation rates in aphotic waters were as high as previous euphotic rates N2 fixation was higher in more ventilated and oxygenated waters containing fresher organic matter Deep N2 fixation contributed largely to depth‐integrated rates and poorly to total nitrogen inputs